Antimicrobial Activity and Mechanism of Action of Dracocephalum moldavica L. Extracts Against Clinical Isolates of Staphylococcus aureus - Yu, Hui; Liu, Min; Liu, Yun; Qin, Lei; Jin, Min; Wang, Zhanli (Frontiers in Microbiology, 2019)
Dracocephalum moldavica L. is a popular traditional medicine used by many countries, which has a wide range of pharmacological effects. The aim of this work was to investigate the antimicrobial effects of D. moldavica L. extracts against clinical isolates of Staphylococcus aureus. Our results demonstrated that the minimal inhibitory concentration (MIC) for 50% and 90% of S. aureus isolates (MIC50 and MIC90) of the ethyl acetate (EtOAc) fraction from D. moldavica L. ethanol extract were 780 g/mL and 1065 µg/mL, respectively. We further observed that the EtOAc fraction disrupted 24 h-biofilm, caused cell membrane damage and irregular cell shape. Additionally, the EtOAc fraction showed slight to moderate toxic effects on human epidermal keratinocyte (HaCaT) cells. Moreover, the results of the differential proteome revealed that 231 proteins were up- regulated while 61 proteins were down-regulated in S. aureus after treatment with the EtOAc fraction. The differentially expressed proteins were functionally categorized by the Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. These proteins contribute to membrane damage, inhibition of biofilm formation and changes in energy metabolism. Thus, the EtOAc fraction of D. moldavica L. ethanol extract, as a natural product, has the potential to be used as an antimicrobial agent to control the clinical isolates of S. aureus.